Potenciali ekološke pridelave za trajnostno lokalno oskrbo s hrano v Sloveniji - Slabe, Anamarija (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2011)
The paper is presenting the assessment of organic production potentials for sustainable local food supply. Using the results of extensive field research among organic farmers, we analyzed the existing organic production for the market by the type of products and marketing channels. We defined the main strengths and weaknesses critical to the development of the Slovenian market for organic food, and highlighted spatial differences. We estimate that, especially in the organic production, there is a large untapped potential for sustainable local food supply in Slovenia.
Keywords: agrarna geografija; agricultural geography; agriculture; ekološko kmetijstvo; food supply; kmetijstvo; organic farming; oskrba s hrano; Slovenia; Slovenija; sonaravni razvoj; sustainable development; trajnostni razvoj